2018
DOI: 10.1021/acs.iecr.8b02994
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Performance of Microfluidic Fuel Cells by Modifying the Carbon-Fiber Paper Cathode by Air Annealing and Acid Oxidation

Abstract: Carbon paper has been widely used as a flow-through electrode to deliver the reactants through the electrodes in microfluidic fuel cells (MFCs). This electrode architecture can utilize the interior area in porous electrodes. Considering its disadvantages, such as a few functional groups, low specific surface area, and poor wetting property, it is necessary to actively treat the carbon paper. We study how the two activation methods, i.e., air annealing and acid oxidation, affect the contents of surface function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 47 publications
0
20
0
2
Order By: Relevance
“…The electrodeposition was also conducted by the electrochemical workstation in a three-electrode system. The palladium catalyst was electrodeposited at 0 V vs Ag/AgCl (in saturated KCl, 0.198 V) until the palladium catalyst loading was 5 mg cm –2 under the assumption that the Coulombic efficiency was 60%. , The detailed surface morphologies and crystal size of the anode palladium catalysts can be found in our previous research. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrodeposition was also conducted by the electrochemical workstation in a three-electrode system. The palladium catalyst was electrodeposited at 0 V vs Ag/AgCl (in saturated KCl, 0.198 V) until the palladium catalyst loading was 5 mg cm –2 under the assumption that the Coulombic efficiency was 60%. , The detailed surface morphologies and crystal size of the anode palladium catalysts can be found in our previous research. , …”
Section: Methodsmentioning
confidence: 99%
“…In MFCs, many oxidants have been studied, such as air, , H 2 O 2 , ClO – , KMnO 4 , VO 2 + , and Fe 3+ . , These oxidants of O 2 , H 2 O 2 , ClO – , and Cr 2 O 7 – require noble or non-noble metals as catalysts to obtain better oxidability. Some oxidants of KMnO 4 and VO 2 + do not need a catalyst but have their own disadvantages when used in MFCs.…”
Section: Introductionmentioning
confidence: 99%
“…Chunmei Liu et al . explored the ways used to raise the performance of MFEFCs with a C fiber cathode 117 . Air annealing and acid oxidation were put into practice, and the scheme of combining the two means would obtain the best performance.…”
Section: Advances In Recent Yearsmentioning
confidence: 99%
“…Chunmei Liu et al explored the ways used to raise the performance of MFEFCs with a C fiber cathode. 117 Air annealing and acid oxidation were put into practice, and the scheme of combining the two means would obtain the best performance. They also studied the influences of different Fe salts on cell performance and confirmed best performance was reached when FeCl 3 was treated as an oxidant.…”
Section: Fabrication Technologies Of Mfefcsmentioning
confidence: 99%
“…When the anolyte and catholyte flow towards the outlet, the fuel and oxidant are largely sequestered to their own sides of the microchannel . This unique feature brings a number of advantages to MFC over the conventional proton exchange membrane fuel cell (PEMFC), such as removal of the need for a membrane, elimination of the membrane‐related problems, and decrease of the fabrication and maintenance cost . However, in the studies, it is found that the diffusion in the direction transverse to the flow creates a mixing region around the laminar interface where the solution contains both fuel and oxidant .…”
Section: Introductionmentioning
confidence: 99%